Association between postoperative delirium and adverse outcomes in older surgical patients: A systematic review and meta-analysis - Yan, Ellene; Veitch, Matthew; Saripella, Aparna; Alhamdah, Yasmin; Butris, Nina; Tang-Wai, David F.; Tartaglia, Maria Carmela; Nagappa, Mahesh; Englesakis, Marina; He, David; Chung, Frances (Journal of clinical anesthesia, 2023)
To assess the incidence of postoperative delirium and its outcomes in older non-cardiac surgical patients. A systematic review and meta-analysis with multiple databases searched from inception to February 22, 2022. Postoperative assessments. Non-cardiac and non-neurological surgical patients aged ≥60 years with and without postoperative delirium. Included studies must report ≥1 postoperative outcome. Studies with a small sample size (N < 100 subjects) were excluded. Outcomes comprised the pooled incidence of postoperative delirium and its postoperative outcomes, including mortality, complications, unplanned intensive care unit admissions, length of stay, and non-home discharge. For dichotomous and continuous outcomes, OR and difference in means were computed, respectively, with a 95% CI. Fifty-four studies (20,988 patients, 31 elective studies, 23 emergency studies) were included. The pooled incidence of postoperative delirium was 19% (95% CI: 16%, 23%) after elective surgery and 32% (95% CI: 25%, 39%) after emergency surgery. In elective surgery, postoperative delirium was associated with increased mortality at 1-month (OR: 6.60; 95% CI: 1.58, 27.66), 6-month (OR: 5.69; 95% CI: 2.33, 13.88), and 1-year (OR: 2.87; 95% CI: 1.63, 5.06). The odds of postoperative complications, unplanned intensive care unit admissions, prolonged length of hospital stay, and non-home discharge were also higher in delirium cases. In emergency surgery, patients with postoperative delirium had greater odds of mortality at 1-month (OR: 3.56; 95% CI: 1.77, 7.15), 6-month (OR: 2.60; 95% CI: 1.88, 3.61), and 1-year (OR: 2.30; 95% CI: 1.77, 3.00). Postoperative delirium was associated with higher odds of mortality, postoperative complications, unplanned intensive care unit admissions, length of hospital stay, and non-home discharge. Prevention and perioperative management of delirium may optimize surgical outcomes. •Pooled incidence of delirium was 19% after elective surgery in older patients.•Pooled incidence of delirium was 32% after emergency surgery in older patients.•Delirium was associated with increased mortality at 1-month, 6-month, and 1-year.•Delirium was associated with increased odds of many adverse postoperative outcomes.